Perceived barriers and facilitators to antiretroviral therapy adherence among youth aged 15-24 years at a regional HIV clinic in SouthWestern Uganda: a qualitative study - Jjumba, Isaac; Kanyesigye, Micheal; Ndagijimana, Gerald; Wattira, James; Olong, Clinton; Olok, Rose Akumu; Beebwa, Esther; Muzoora, Conrad (African Health Sciences, 2022)
Introduction: South-Western region has the second highest HIV prevalence in Uganda. Youth aged 15-24 have shown poor adherence to antiretroviral therapy compared to the older cohorts. Previous studies from other regions have shown various barriers and facilitators. Our study was designed to describe specific barriers and facilitators to treatment adherence among youths in a large regional HIV clinic in southwestern Uganda. Methods: We used a phenomenological qualitative study design conducted amongst 30 purposively selected HIV positive youth aged 15-24 years enrolled at Mbarara Regional Referral Hospital HIV clinic on ART for a period of at least one year and 6 key informants using in-depth interviews. The data was collected in an inductive manner during the period between 21st July and 17th August 2020. The recordings were backed up, transcribed verbatim and then analyzed manually using thematic content analysis. Results: The barriers to ART adherence were described in three descending categories as perceived treatment burden, perceived resultant stigma and discrimination, whereas the main facilitators were; perceived usefulness of HIV medications, availability of free services and Social support Conclusion: Youths aged 15-24 have challenges with ART associated treatment burden and fear to disclose their HIV status because of the resultant stigma from their communities. Many have however accepted the fact that HIV medications are lifesaving and are strongly motivated to adhere to their medications despite the circumstances
Keywords: Barriers; Facilitators; Adherence; HIV/AIDS; Young Adults